Tinjauan Tingkat Pengetahuan Hygiene Makanan Pedagang Sala Lauak Di Objek Wisata Ulakan Padang Pariaman - Ali, Abi Al-Sobar; Kasmita; Susanti, Retnaningtyas; Lisna, Yuke Permata (Jurnal Kajian Pariwisata Dan Perhotelan, 2024)
Abstract: This study originated from the fact that only 10% of the 40 sala lauak vendors at Ulakan Padang Tourism Object apply good food hygiene standards. This study was conducted to evaluate the level of understanding of food hygiene of food vendors in the Ulakan tourist area of Padang Pariaman. The research method used was quantitative with descriptive data. This study was conducted in Ulakan tourism destination in Padang Pariaman District. The number of participants in this study was 40 vendors operating in the Ulakan Tourism area. They became the main sample in data collection using a questionnaire based on the Guttman scale model. According to the results of the study, the level of knowledge about food hygiene at Ulakan tourist attraction in Padang Pariaman showed that 60% were in the poor category, 17% were in the moderate category, and 24% were in the good category.